2012
DOI: 10.14411/eje.2012.044
|View full text |Cite
|
Sign up to set email alerts
|

Does monogeny enable gall midges (Diptera: Cecidomyiidae) to regulate their sex ratio?

Abstract: Abstract. Monogeny, the production of unisexual broods by individual females, is widely recorded in gall midges (Diptera: Cecidomyiidae). Theoretical models propose that the adjustment of offspring sex ratio by females may pre-dispose the evolution of monogeny in gall midges however empirical studies in this field are superficial. Expressed more simply, monogeny may enable individual female gall midges to decrease or increase the number of male and female progeny they produce in response to changes in environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…Cecidomyiidae) une cécidomyie prédatrice des pucerons du cotonnier, Tabadkani et al (2012) ont conclu que les femelles ne régulaient pas le nombre de mâles et de femelles de leurs descendances en réponse au changement dans l'abondance de leurs proies. Selon Sanchez (2008), le règne animal possède un trésor de mécanismes à travers lesquels le sexe est déterminé et tous ces mécanismes sont représentés dans la classe des insectes.…”
Section: Discussionunclassified
“…Cecidomyiidae) une cécidomyie prédatrice des pucerons du cotonnier, Tabadkani et al (2012) ont conclu que les femelles ne régulaient pas le nombre de mâles et de femelles de leurs descendances en réponse au changement dans l'abondance de leurs proies. Selon Sanchez (2008), le règne animal possède un trésor de mécanismes à travers lesquels le sexe est déterminé et tous ces mécanismes sont représentés dans la classe des insectes.…”
Section: Discussionunclassified
“…However, our results show that differential lifespan of sexes are sufficient to explain the occurrence of female biased sex ratio in natural populations of gall midges. The sex ratios of A. aphidimyza have been reported to vary from 45% to 72% females in both natural populations (Havelka & Zemek 1999) and laboratory or commercially reared colonies (Gilkeson & Hill 1986; Heimpel & Lundgren 2000; Tabadkani et al . 2012).…”
Section: Discussionmentioning
confidence: 99%
“…2004). Although, several studies have suggested that the sex ratio of A. aphidimyza in laboratory and commercially reared colonies is slightly male‐biased (Gilkeson & Hill 1986; Heimpel & Lundgren 2000; Tabadkani et al . 2012), some other studies propose a female‐biased sex ratio (47% to 72% females) in natural populations of this species (Havelka & Zemek 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation